Placental damage in pregnancies with systemic lupus erythematosus: A narrative review - Castellanos Gutierrez, Aleida Susana; Figueras, Francesc; Morales-Prieto, Diana M.; Schleußner, Ekkehard; Espinosa, Gerard; Baños, Núria (Frontiers in Immunology, 2022)
Systemic lupus erythematosus (SLE) is a chronic inflammatory autoimmune disease of unknown cause, which mainly affects women of childbearing age, especially between 15 and 55 years of age. During pregnancy, SLE is associated with a high risk of perinatal morbidity and mortality. Among the most frequent complications are spontaneous abortion, fetal death, prematurity, intrauterine growth retardation (FGR), and preeclampsia (PE). The pathophysiology underlying obstetric mortality and morbidity in SLE is still under investigation, but several studies in recent years have suggested that placental dysfunction may play a crucial role. Understanding this association will contribute to developing therapeutic options and improving patient management thus reducing the occurrence of adverse pregnancy outcomes in this group of women. In this review, we will focus on the relationship between SLE and placental insufficiency leading to adverse pregnancy outcomes.